Improving performance of switched reluctance motor by fuzzy logic controller - Derdiyok, A.; Inanc, N.; Özbulur, Veysel; Bilgiç, Mehmet Oruç (My University, 1999)
This paper presents torque ripple minimization of a switched reluctance motor (SRM) by using a fuzzy controller, The nonlinear model of the SRM and the mathematical model of the converter circuit are driven. The motor used in both simulation and experiment is an 8/6 four phase SRM with a C-Dump converter. The applied fuzzy controller adjusts the value of the reference current to keep the speed of the motor constant. The results show that the fuzzy logic is effective in reducing the torque ripple of the motor, and compensating for the nonlinear torque characteristics. The experimental result is given for a current control algorithm, and it shows that the quite nonlinear model of the SRM is well defined.
Keywords: Switched reluctance motor; fuzzy logic control; torque ripple reduction; C-Dump converter circuit